Family caregiving burden: spiritual well-being and resilience in caring for older people with functional deficits among Felda settlers in Kuantan, Pahang - Nik Mohd Hatta, Nik Noor Kaussar; Abdul Wahab, Patimah; Nik Kamiluddin, Nik Nurfathiah Sa’adah (IIUM Press, 2024)
PURPOSE: This study aimed to identify the connection between caregiver sociodemographic characteristics, health status, caregiving demands, spiritual well-being, resilience, and caregiving burden in caring for older people with functional deficits in Felda Territory of Kuantan, Pahang. METHODS: A cross-sectional study with cluster random sampling was conducted to select caregivers of older adults with functional deficits in Felda Territory, Kuantan, Pahang. Felda, a naturally occurring group, was randomly chosen from three populations representing the area. Self-administered questionnaires covering sociodemographic information, caregiving demands, JAREL Spiritual Well-being Scale, Connor-Davidson Resilience Scale (CD-RISC), and Zarit Burden Interview (ZBI) were distributed to residents via the Felda office. Data were analyzed using descriptive statistics and the Pearson Chi Square test in SPSS version 26. RESULTS: The majority of participants were female caregivers, who experienced a higher caregiving burden than male caregivers. No significant associations were found between caregiver sociodemographics, caregiving demand, and caregiving burden. Caregiver spiritual well- being was not linked to caregiving burden, but caregiver resilience was significantly associated with a lower caregiving burden. Specifically, 4% of caregivers with low spiritual well-being and 1.6% with high resilience reported severe caregiving burden. CONCLUSION: The findings suggest the need for further intervention in addressing the caregiving burden among caregivers in Malaysia.